Individual Ambidexterity and Organizational Performance Among Employees - De Juan, Lenie (Journal of Interdisciplinary Perspectives, 2025)
This study aimed to assess if individual ambidexterity and organizational performance were symbiotic and how uncommon talent helped teams and businesses achieve unprecedented success among outlets of BB Corp. in a quantitative approach. It also tried to figure out the effects of these practices on business performance, specifically profitability and sustainability. With all the challenges encountered by employees and organizations, there was a need to develop awareness and understanding of how ambidexterity affects organizational performance that keeps individuals guided and performing well. This study used a descriptive causal design. The total population was 100 respondents, and a total enumeration sampling technique was applied. The result showed a significant relationship between the manifestation of Individual Ambidexterity and organizational performance level among employees in BB Corp. It also indicated that in terms of Exploration, the general assessment was interpreted as Fully Manifested, while in terms of Exploitation, it was interpreted as Manifested. In terms of Financial, Operational, and Shareholder Return Performance, these are all interpreted as Good. Exploitation significantly impacts the organizational performance level among employees in terms of Financial and Operational Performance. While in Shareholder Return Performance, exploration and exploitation significantly impact the Organizational Performance. This also indicates that the higher the manifestation of Individual Ambidexterity, the higher the organizational performance. The proposed action plan can address the issues and challenges of individual ambidexterity to enhance employee organizational performance. It served as a basis for management practices once found compelling.